Lycophytes and ferns composition of Atlantic Forest conservation units in western Paraná with comparisons to other areas in southern Brazil - Lautert,Mayara (2015)
This study surveyed lycophyte and fern species in four forest fragments in western Paraná, Brazil, and compared them to 15 other fragments with different plant formations from the Atlantic Forest biome in southern Brazil. In total, five lycophyte species (in two families and two genera) and 98 species and two varieties of ferns (in 16 families and 38 genera) were registered in the four fragments. The most represented families were Pteridaceae (23 spp.), Polypodiaceae (18 spp.), Aspleniaceae (13 spp.), and Thelypteridaceae (11 spp.). Asplenium (12 spp.), Thelypteris (10 spp.), and Blechnum (seven spp.) were among the most represented genera. The occurrence of Dicksonia sellowiana was noteworthy because it was associated with seasonal semideciduous forest and is threatened in Brazil. Similarity among areas was determined by a cluster analysis (UPGMA and Sørensen’s index) and the relation between similarity and geographic distance was determined through Matel’s analysis. The analyses revealed greater similarity among the four study areas and, for these areas as a whole, greater similarity to fragments in Rio Grande do Sul, which is evidence that these areas have similar environmental conditions.